Perbedaan Lama Waktu Tunggu, Biaya dan Mutu Pelayanan Kesehatan Gigi di Rumah Sakit Pemerintah dan Swasta : Analisis Manajerial - Julita Hendrartini; Laksono Trinantoro (Faculty of Dentistry, Universitas Indonesia, 2015)
The increase demand for high quality dental care requires managerial improvement at hospital. This research aims to identify the difference of dental patient waiting time, cost and quality care between public and private hospital. A cross sectional design was used in this research, with 100 samples in public and private hospital respectively. The result shows that the waiting time at public hospital was 2.5 longer than in private one. Perception on cost and quality of care at public hospital were lower than at private hospital diffrences were statistically significant at p=0.001.